Cost-Efficient Treatment of Acidic Spent Electrolyte Using Alkaline Neutralization and Pressure Filtration in Precious-Metal Refining - Handayani, Lidya; Andarista, Oktaviani (Journal of Community Based Environmental Engineering and Management, 2026)
This study aims to evaluate the technical performance and cost efficiency of an integrated alkaline neutralization and pressure filtration system for eliminating hazardous liquid waste generated from acidic spent electrolyte in a precious-metal refining facility operating under a zero-liquid-discharge configuration. A field-scale quasi-experimental study was conducted at PT X, Indonesia, using NaOH conditioning followed by constant-pressure filtration at approximately 7000 psi. The objective was to determine the optimum operating conditions capable of transforming hazardous liquid waste into a stable solid residue while minimizing waste volume and handling costs. Results show that a NaOH dosage of 100 kg per batch produced a dense, filterable sludge, and that a filtration time of 60 minutes yielded the best dewatering performance. The initial sludge moisture content exceeded 20%, while the optimized process reduced the final moisture content to 14.36%, forming a compact and mechanically stable cake suitable for safe handling. On a system level, the treatment converted 730 m³/year of liquid hazardous waste into only 45.1 m³/year of dewatered sludge, representing a 94% reduction in off-site waste volume. Laboratory analysis confirmed effective metal immobilization, with sludge containing 23.64% Cu, 463 mg/kg Ag, and 1 mg/kg Au. The findings demonstrate that the NaOH-assisted filter press functions not only as a dewatering unit but as a strategic hazardous waste minimization tool. By eliminating the liquid phase and stabilizing metal-bearing residues, the system improves operational safety, regulatory compliance, and economic performance.